2021
DOI: 10.3390/ma14092371
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Undercut Anchor Head Angle on the Propagation of the Failure Zone of the Rock Medium

Abstract: The paper presents the results of a numerical analysis (FEM) describing the effect of the undercutting head angle on the formation of the rock mass failure zone during the initial stages of failure propagation. The research was carried out in the context of developing a technology for rock extraction by controlled pull-out of undercut anchors installed in the rock mass. The focus was on the initial stage of crack propagation and its trajectory for anchors embedded at an assumed constant depth and a value of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…For small head values, a large contribution of tensile circumferential stresses in the anchor–media contact zone has been demonstrated, leading to a faster destruction of the medium and a reduction in the anchor load capacity. The work of Jonak et al [ 31 ] has shown a significant influence of the head angle on the formation of the detachment range (potentially the volume of detached solids). The value of the undercutting head angle depends to a large extent on the correctness of its installation and, in the case of the non-conventional technology of tearing off postulated by the authors, also on the wear process of the conical part of the undercutting head.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For small head values, a large contribution of tensile circumferential stresses in the anchor–media contact zone has been demonstrated, leading to a faster destruction of the medium and a reduction in the anchor load capacity. The work of Jonak et al [ 31 ] has shown a significant influence of the head angle on the formation of the detachment range (potentially the volume of detached solids). The value of the undercutting head angle depends to a large extent on the correctness of its installation and, in the case of the non-conventional technology of tearing off postulated by the authors, also on the wear process of the conical part of the undercutting head.…”
Section: Discussionmentioning
confidence: 99%
“…Anchor: Element type: CAX4R. The sensitivity of the model to the finite element mesh discretization method was evaluated using 6 mesh types [31]. The size of the mesh elements Δ was varied along the form of a hypothetical cone angle (inclined at an angle in the model, Figures 5 and 7).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations